Environmental performance and stakeholders’ pressure against the small batik enterprises in Kelantan, Malaysia - Yaacob, Mohd Rafi; Ismail, Mohammad; Zakaria, Mohd Nazri; Mat Zin, Nur Faizah; Abdul Rahim, Mohammad Nizamuddin (Universiti Malaysia Kelantan, 2017)
The aims of this paper are to investigate environmental performance as well as stakeholders’ pressure against Batik enterprises in Kelantan. Based on the survey on 36 small Batik entrepreneurs, only 5 enterprises (13.5%) achieved high environmental performance and the rests (86.5%) were categorised as low environmental performance enterprises. These findings come as no surprise because the majority of Batik enterprises perceived low pressure from stakeholders, including regulatory pressure which usually exerts high pressure on businesses on other industries in Malaysia and other countries. The conclusion of this study is instructive, demanding the players in the industry to be environmentally proactive; however, this does not come easily unless they will be rewarded as being environmentally friendly and will pay heavy consequences of not being so.